Popular Musical Performing Arts and their Role in Shaping Intangible Heritage in the Kingdom of Saudi Arabia (The International Journal of Educational Sciences and Arts, 2024)
This study addresses the challenges facing the proper protection of heritage and the proper employment of intangible heritage. One of the most prominent of these challenges is the nature of intangible heritage, as it is a living and changing heritage and there are fears of its distortion, deformation and isolation from the context of the known, so that it appears in the form of vulgar products that lack authenticity. In these lines, we will explain how performing arts of various types, especially folk heritage, folk songs and dances, have contributed to the formation of intangible heritage and its proper employment and how they have worked to preserve it.Study methodology: This study followed the descriptive analytical approach based on presenting and analyzing information in order to reach realistic scientific results.
Keywords: Intangible Heritage; Performing Arts; Music; Protection; Employment; Saudi Arabia